2022
DOI: 10.1200/edbk_349509
|View full text |Cite
|
Sign up to set email alerts
|

New Directions for Mantle Cell Lymphoma in 2022

Abstract: Mantle cell lymphoma is a rare B-cell non-Hodgkin lymphoma that is clinically and biologically heterogeneous. Risk stratification at the time of diagnosis is critical. One of the most powerful prognostic indices is the Mantle Cell Lymphoma International Prognostic Index-Combined, which integrates an estimate of proliferation (Ki67 index) with the standard Mantle Cell Lymphoma International Prognostic Index clinical factors. In addition, the presence of TP53 mutation is associated with suboptimal response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…To date, no therapeutic immunochemotherapies have been found to overcome the TP53 aberrancy in MCL patients, 36–38 despite the potential of chimeric antigen receptor T‐cell (CART) therapy that still requires more clinical validation 8,39,40 . In the present study, we found that in TP53 wild MCL cell (JVM‐2), depletion of TP53 can significantly up‐regulated cytidine metabolism, leading to the hypothesis that CTPS1 inhibition might overcome TP53 aberrancy in MCL patients.…”
Section: Discussionmentioning
confidence: 69%
“…To date, no therapeutic immunochemotherapies have been found to overcome the TP53 aberrancy in MCL patients, 36–38 despite the potential of chimeric antigen receptor T‐cell (CART) therapy that still requires more clinical validation 8,39,40 . In the present study, we found that in TP53 wild MCL cell (JVM‐2), depletion of TP53 can significantly up‐regulated cytidine metabolism, leading to the hypothesis that CTPS1 inhibition might overcome TP53 aberrancy in MCL patients.…”
Section: Discussionmentioning
confidence: 69%
“…Aberrations of the TP53 gene are well established as a predictor of aggressive disease course, resistance to standard immunochemotherapy and inferior survival 33,34 . Aberrations may occur due to either deletion of 17p (del17p, detected using FISH or single‐nucleotide polymorphism array analysis) and/ or a mutation in the TP53 gene (assessed by next‐generation sequencing [NGS] or reverse transcription‐polymerase chain reaction) 35 . TP53 gene alterations promote genomic instability, cell cycle upregulation, inhibition of apoptosis and higher proliferation 36 .…”
Section: Aggressive MCLmentioning
confidence: 99%
“…33,34 Aberrations may occur due to either deletion of 17p (del17p, detected using FISH or single-nucleotide polymorphism array analysis) and/ or a mutation in the TP53 gene (assessed by next-generation sequencing [NGS] or reverse transcription-polymerase chain reaction). 35 TP53 gene alterations promote genomic instability, cell cycle upregulation, inhibition of apoptosis and higher proliferation. 36 p53 expression using immunohistochemistry (IHC) has been demonstrated to be a surrogate marker for TP53 deletion or mutation, with a series of 365 patients from the European Mantle Cell Lymphoma Network (EMCLN) demonstrating high p53 expression to be prognostic for both inferior timeto-treatment failure and OS on analyses adjusted for MIPI score and Ki-67.…”
Section: Genetic Aberrationsmentioning
confidence: 99%
“…1C ), immunophenotype, proliferative index (labeling of Ki67) (Fig. 1D ) and presence of TP53 deletions/mutations since the occurrence of one or more of these variables associates with a poor prognosis [ 81 , 85 ]. Notably, TP53 deleted/mutated cases are usually resistant to chemotherapy but are sensitive to BTKi [ 82 , 83 ] or CAR-T cells [ 81 ].…”
Section: Mature B-cell Neoplasmsmentioning
confidence: 99%